2012
DOI: 10.1007/s10286-012-0176-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporary elimination of orthostatic hypotension by norepinephrine infusion

Abstract: A cardinal manifestation of chronic autonomic failure is neurogenic orthostatic hypotension (OH), which often is associated with supine hypertension, posing a therapeutic dilemma. We report here success in a first step toward development of a “prosthetic baroreceptor system” to maintain blood pressure during orthostasis without worsening supine hypertension. In all of four patients with neurogenic OH, titrated i.v. NE infusion kept directly recorded intra-arterial pressure at or above baseline during progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This study showed drastic increases in Epi before syncopal episodes, suggesting that vasodilation in neurocardiogenic syncope is, at least in part, humorally mediated (10,18). Furthermore, intraveneous infusion of NE maintained BP in OH subjects during HUT, temporarily eliminating OH (19). Thus, the imbalance of NE and Epi, with higher circulating Epi, most likely contributes to vasodilation or impairments in peripheral vascular resistance by stimulating vasodilating ␤ 2 -adrenergic receptors in skeletal blood vessels, which results in low BP/cardiac output in OH and syncope subjects (15).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This study showed drastic increases in Epi before syncopal episodes, suggesting that vasodilation in neurocardiogenic syncope is, at least in part, humorally mediated (10,18). Furthermore, intraveneous infusion of NE maintained BP in OH subjects during HUT, temporarily eliminating OH (19). Thus, the imbalance of NE and Epi, with higher circulating Epi, most likely contributes to vasodilation or impairments in peripheral vascular resistance by stimulating vasodilating ␤ 2 -adrenergic receptors in skeletal blood vessels, which results in low BP/cardiac output in OH and syncope subjects (15).…”
Section: Discussionmentioning
confidence: 55%
“…The neurohumoral profile included measurements of circulating catecholamines (Epi and NE), the renin-angiotensin-aldosterone system axis, and AVP to provide a comprehensive panel for subjects with OI to test the effects of orthostatic challenge. Our methodology was unique in that the neurohumoral profile was measured during HUT as opposed to previous studies in adults in which sample collection was taken in the supine position alone, after completion of a 30-min test, or after an evoked HUT response (11,19,20,34,37). Our approach aimed to more accurately reflect real-time neurohumoral changes as they related to cardiovascular symptoms including HR and BP changes, especially for neurohumoral factors that are less stable and metabolized quickly (1).…”
Section: Discussionmentioning
confidence: 99%
“…Carotid sinus stimulation or renal sympathetic radiofrequency ablation may attenuate refractory hypertension (Krum et al, 2009; Lohmeier et al, 2011). Intravenous infusion of norepinephrine or an automated abdominal binder may mitigate neurogenic orthostatic hypotension (Goldstein et al, 2012; Okamoto et al, 2016; Polinsky et al, 1983; Zekeridou et al, 2015); and vagus nerve stimulation, by directly or reflexively evoking effects on elaboration of cytokines, may be useful to treat conditions involving auto-immunity such as rheumatoid arthritis (Koopman et al, 2016). …”
Section: 20 Cybernetic Medicine (Scientific Integrative Medicine)mentioning
confidence: 99%